Synthesis and characterization of transitional metal polypyridine complex fullerene salts - Hong, Jie, author; Elliott, C. Michael, advisor; Prieto, Amy Lucia, committee member; Van Orden, Alan K., committee member; Ladanyi, Branka M., committee member; Hochheimer, Hans D., committee member (Colorado State University. Libraries, 2010)
In recent years, ionic fullerene (C60) salts have attracted much attention due to their interesting chemical and physical properties. Transition metal polypyridine complex, most notably, tris (2, 2'-bipyridine)ruthenium-based compounds, [RuL3]m+, have a number of photochemical and electrochemical properties which make them of interest for both fundamental and applied studies. The similarity of electrochemical potentials of [RuL3] and C60"’ gives rise to the possibility of a new charge-transfer ionic salts [Ru L3m+]n(C6on-)m- In chapter I, the background of ionic C60 salts as well as the motivation of preparing transition metal polypyridine complex C60 salts is described in detail. A chart of electrochemical data is generated and used as a guideline to predict the possible stoichiometries of ionic salts throughout the whole research work. In Chapter II, the synthesis and characterization of three ionic salts using [Ru(bpy)3]m+ (m = 1, 2) as cations are fully described. All three salts are semiconducting with the highest conductivity at ~ 10 S • m-1. Interesting paramagnetism is reported as well. The detailed discussions based on single crystal and powder X-ray diffraction studies are useful in better understanding the electronic conduction and magnetism. The physical properties of ionic C60 salts can be rationalized based on the crystal packing. In the presence of a bulky cation Ru(bpy)3m+, an expanded crystal lattice is found with weak site-site interactions. In Chapter III, the ligand substitution effect of [RuL3 m+]n(C60n-)m is examined. Four ligands: 4, 4'-dimethyl-2, 2'-bipyridine (4DMB), 5, 5'-dimethyl-2, 2'-bipyridine (5DMB), 4, 4'-di-tert-butyl-2, 2'-bipyridine (TBB) and 4, 4', 5, 5'-tetramethyl-2, 2'- bipyridine (TMB) are chosen as the targets. The ligand substitution not only changes the redox potentials of cation Ru(bpy)3m1 but also alters its size. This provides a route for tuning the properties of [RuL3 ’”^]n(C6on-)m • Electrical and magnetic properties of all compounds as prepared are investigated. The highest conductivity found is also close to 10 S • m-1. In Chapter IV, the effect of substituting ruthenium by chromium in metal complex ionic C60 salts is studied. Cr(bpy)3 m+ and Ru(bpy)3 m+ are very similar in size but of quite different redox potentials. The electrical conductivity of their corresponding ionic salts shows large dependence on the redox potentials.
Covers not scanned.
Keywords: Transition metal complexes; Ruthenium compounds; Fullerenes